HycycleS: a project on nuclear and solar hydrogen production by sulphur-based thermochemical cycles. (1st January 2011) - Roeb, M.; Thomey, D.; Graf, D.; Sattler, C.; Poitou, S.; Pra, F.; Tochon, P.; Mansilla, C.; Robin, J-C.; Le Naour, F.; Allen, R.W.K.; Elder, R.; et al.
The European FP7 project HycycleS focuses on providing detailed solutions for the design of specific key components for sulphur-based thermochemical cycles for hydrogen production. The key components necessary for the high temperature part of those processes, the thermal decomposition of H2 SO4, are a compact heat exchanger for SO3 decomposition for operation by solar and nuclear heat, a receiver-reactor for solar H2 SO4 decomposition, and membranes as product separator and as promoter of the SO3 decomposition. Silicon carbide has been identified as the preferred construction material. Its stability is tested at high temperature and in a highly corrosive atmosphere. Another focus is catalyst materials for the reduction of SO3 . Requirement specifications were set up as basis for design and sizing of the intended prototypes. Rigs for corrosion tests, catalyst tests and selectivity of separation membranes have been designed, built and completed. Prototypes of the mentioned components have been designed and tested.